Optimalisasi Parkir Mobil di Monkey Forest Ubud Kabupaten Gianyar - Kurniadewi, Anak Agung Dinda; Krisnandika, Anak Agung Keswari (Nandur; Vol 3 No 4 (2023), 2023)
Monkey Forest is a tourism destination located in Ubud, Gianyar Regency, Bali. Monkey Forest has parking facilities which is used to park Transportation for tourists visiting Monkey Forest tourism destinations. Monkey Forest Parking is the main access to Monkey forest tourism destinations, because the Lobby is located in the parking lot. This study aims to determine parking management in the monkey forest and determine the capacity of the transprortations that can park in existing parking lots. The research method used is by observing and interviews. The results obtained in this study are recommendations to the manager about optimalization Types of transportation parked in the monkey forest parking lot between other passenger cars and medium vehicles. Recommendations that can be given in this study are the provision of road markings for parking and classifying parking based on the type of vehicle.